SUSTAINABLE FDI FOR SUSTAINABLE DEVELOPMENT IN VIETNAM - Vo, Vy (My University, 2021)
Foreign direct investment (FDI) is a widely discussed topic. Although FDI is expected to con-tribute positively to host country development, the degree of influence and specific impact is different. In the absence of effective monitoring and management, FDI can also bring about an adverse reaction that affects the economic and social development or affects the re-sources and environment of the host country. According to the current development trend, FDI attraction has shifted from economic focus to sustainable development, leading to the concept of sustainable FDI. An investment is described as sustainable FDI as it positively con-tributes to the host country's economic, social and environmental development while also practising good governance (Sauvant and Mann, 2020). The attraction of sustainable FDI is expected to bring potential contributions to green growth / sustainable development in to-day's vulnerable world. Vietnam is seen as a bright spot for foreign investors, yet attracting and using FDI in Vietnam is assessed as lacking effectiveness (quantity over quality). Therefore, Sustainable FDI is a solution for Vietnam to promote high economic growth while ensuring social and environmental stability. The study is conducted to analyze the impact of SFDI on the sustainable development of Vietnam. The results show that attracting and utilising sustainable FDI is the right direction that Vietnam needs to move towards as it contributes to long-term economic development (by increasing capital, employment, increasing linkages effects with local businesses, transferring technology, etc.). Meanwhile, it promotes social sustainable development (proactively implementing CSR, improving the quality of human resources, etc.) without harming the environment and natural resources of the host country (appropriate resource management, efficient treatment and treatment of water, emissions, renewable energy projects etc). Later, proposals to identify and attract MNEs engaging in sustainable investment projects are suggested.
Keywords: foreign investments; Vietnam; sustainable development; international corporations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business